THE INFLUENCE OF THE COVID-19 PANDEMIC ON THE CORPORATE CULTURE FORMATION AND DEVELOPMENT - IVANCHENKO, HALYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the importance of corporate culture in the company. The main structural elements of corporate culture are identified. It is established what features are situational factors on the organizational culture implemented in the company. Corporate culture is formed under the influence of natural and directed factors. The first are the external environment in which the organization operates, including social norms, market and economic situation, the place of organization in society. The second group of factors that produce the company’s culture are purposeful actions of management and employees. Situational factors under the influence of which the corporate culture in business currently operates influence the behavior of both the individual employee and the team as a whole. In the most effective organizations, culture supports and promotes the goals and strategies of the company. Standards and expectations help employees work to achieve company success. It is also noted that for the maintenance and development of corporate culture in the context of the COVID-19 pandemic, such components as corporate values, the role of leader and the brand of the employer are important. Corporate values, which are spelled out in internal documents and transmitted to employees on a periodic basis, form the company’s reputation. Leadership serves as a behavioral guideline in the activities of the company’s employees, allows to increase their productivity. The brand of the employer is an important factor that determines the external and internal image of the organization in the long run. It is suggested that in order to improve the existing or form a new corporate culture, the company should conduct a detailed analysis of changes in the organization, eliminate outdated practices that have lost their meaning and get feedback from employees on the main key elements of a new or improved corporate culture. Corporate culture management is an important element in the life of the company. Diagnosis of corporate culture allows you to determine the strength of the company’s culture, which, in turn, makes it possible to predict the stability of the company under the influence of external and internal destructive factors.